Directional predictability in foreign exchange rates of emerging markets: New evidence using a cross-quantilogram approach - Mohd Ziaur Rehman; Aviral Kumar Tiwari; Durga Prasad Samontaray (Borsa Istanbul Review, 2022)
This study investigates the directional predictability of exchange rates in emerging markets. Using a cross-quantilogram model, we show that dependencies among emerging markets exchange rates are heterogeneous. Specifically, the Mexican peso, Brazilian real, and Turkish lira are leading emerging market currencies that provide hedging opportunities for currency investors. The structural dependencies across the pairs of exchange rates are evident at lag 1, and the relationships dissipate at longer lags. Secondly, the partial cross-quantilogram results indicate that oil is not a driving force of interrelationship among the exchange rates. Furthermore, the estimations of cross-quantile correlations from recursive subsamples reveal time-variant traits. If policymakers and financial regulators focus on comovements among emerging market currencies and distinguish net recipients from net transmitters in different environments, they can devise a surveillance system to adjust the market interdependence effects across emerging market foreign exchange rates. Therefore, they can promote the stability of emerging market currencies.